The Impact of Signal Strength over Routing Protocols in Wireless Networks - Dr. Reem Jafar Ismail (International Journal of Engineering and Management Research, 2018)
In ad hoc routing protocols the source node may need an intermediate nodes to transmit the packets into the destination if the destination is not within transmission range of the source. This paper studies the impact of signal strength of nodes over ad hoc routing protocols and explains an important effect of signal strength on ad hoc routing protocols in four different directions including the routes and the nodes. As a result the study give an important improvement in ad hoc routing protocols when using signal strength compared to other ad hoc routing protocols without considering signal strength.